Peran Kuning Telur pada Medium Simpan Beku Semen TES-Tris Yolk Citrat terhadap Motilitas dan Vitalitas Spermatozoa Manusia Post Freezing. - Djaelani, Muhammad Anwar (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
The aim of this research was to examine the possibility of semen cryopreservation using TES-Tris yolk citrat (TES-TYC) medium without egg yolk. Semen fulfilling inclusion criteria with WHO criteria was divided into two groups. The semen was then mixed with TES-TYC medium and TES-TYC medium without egg yolk and cryopreserved in liquid nitrogen. After one mounth the semen was thawed and recount its sperm motility and vitality. Data obtained showed that the motility and vitality of post freezing sperm cryopreserved with TES-TYC medium was higher compared to TES-TYC medium without egg yolk. It could be concluded that the existenced of egg yolk in TES-TYC medium was kept sperm integrity during cryopreservation, hence the existenced of egg yolk as ingredient in TES-TYC medium was needed.